Laser speckle imaging for visualization of hidden effects for early detection of antibacterial susceptibility in disc diffusion tests - Balmages, Ilya; Reinis, Aigars; Kistkins, Svjatoslavs; Bliznuks, Dmitrijs; Plorina, Emilija Vija; Lihachev, Alexey; Lihacova, Ilze (Frontiers in Microbiology, 2023)
Rapid identification of effective antibiotic treatment is crucial for increasing patient survival and preventing the formation of new antibiotic-resistant bacteria due to preventative antibiotic use. Currently utilized "gold standard" methods require 16-24 hours to determine the most appropriate antibiotic for the patient's treatment. The proposed technique of laser speckle imaging with subpixel correlation analysis allows for identifying dynamics and changes in the zone of inhibition, which are impossible to observe with classical methods. Furthermore, it obtains the resulting zone of inhibition diameter earlier than the disk diffusion method which is recommended by the European Committee on Antimicrobial Susceptibility Testing (EUCAST). These results could improve mathematical models of changes in the diameter of the zone of inhibition around the disc containing the antimicrobial agent, thereby speeding up and facilitating epidemiological analysis.